Orthographic Consistency and Word-Frequency Effects in Auditory Word Recognition: New Evidence from Lexical Decision and Rime Detection - Petrova, Ana; Gaskell, Gareth; Ferrand, Ludovic (Frontiers in Psychology, 2011)
Many studies have repeatedly shown an orthographic consistency effect in the auditory lexical decision task. Words with phonological rimes that could be spelled in multiple ways (i.e., inconsistent words) typically produce longer auditory lexical decision latencies and more errors than do words with rimes that could be spelled in only one way (i.e., consistent words). These results have been extended to different languages and tasks, suggesting that the effect is quite general and robust. Despite this growing body of evidence, some psycholinguists believe that orthographic effects on spoken language are exclusively strategic, postlexical or restricted to peculiar (low-frequency) words. In the present study, we manipulated consistency and word frequency orthogonally in order to explore whether the orthographic consistency effect extends to high-frequency words. Two different tasks were used: lexical decision and rime detection. Both tasks produced reliable consistency effects for both low- and high-frequency words. Furthermore, in Experiment 1 (lexical decision), an interaction revealed a stronger consistency effect for low-frequency words than for high-frequency words, as initially predicted by Ziegler and Ferrand (1998), whereas no interaction was found in Experiment 2 (rime detection). Our results extend previous findings by showing that the orthographic consistency effect is obtained not only for low-frequency words but also for high-frequency words. Furthermore, these effects were also obtained in a rime detection task, which does not require the explicit processing of orthographic structure. Globally, our results suggest that literacy changes the way people process spoken words, even for frequent words.